Antibiotics resistance - a stumbling block to antibiotics research - Sivasankari Marimuthu,; Arul Jayanthi Antonisamy,; Sankar Malayandi,; Karthikeyan Rajendran, (International Journal of Research in Pharmaceutical Sciences, 2019)
Antibiotics are natural or synthetic substances that inhibit the growth of infectious microorganisms and prevent from them, causing serious infections. Though the discovery of penicillin was claimed to be accidental, later on, systematic procedures for antibiotic discovery was introduced by Waksman through his streptomycin discovery. Adopting Waksman's platform, many researchers are exploring natural sources in search of antibiotics. On the other hand, the development of resistance to antibiotics is growing at a rate faster than the discovery of new antibiotics. While a number of semi synthetic and synthetic compounds with antimicrobial properties are emerging to combat the above problem, the microorganisms are in no way working inferior to resist the actions of such substances. In fact, the development of resistance by microorganisms to above said alternatives are observed at an even faster rate than the natural antimicrobial compounds obtained from microbes. The reason behind such a faster resistance development is due to the similar structural features of semi-synthetic and synthetic compounds to natural antibiotics from microbes. The treatment of infectious diseases becomes a big task and requires a greater concern nowadays to avoid increased rates of mortality. This is an alarming condition demanding for the discovery and development of new antimicrobial compounds that would end up as a better solution for the existing problem and avoid the development of resistance. This review presents the background of antibiotics discovery and resistance development and also provides an insight into the available strategies to combat the problem.